2016
DOI: 10.1093/humrep/dew214
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of ‘one-step’ versus ‘sequential’ embryo culture conditions through embryonic genome methylation and hydroxymethylation changes

Abstract: STUDY QUESTIONIn comparison to in vivo development, how do different conditions of in vitro culture (‘one step’ versus ‘sequential medium’) impact DNA methylation and hydroxymethylation in preimplantation embryos?SUMMARY ANSWERUsing rabbit as a model, we show that DNA methylation and hydroxymethylation are both affected by in vitro culture of preimplantation embryos and the effect observed depends on the culture medium used.WHAT IS KNOWN ALREADYCorrect regulation of DNA methylation is essential for embryonic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…In bovine oocytes, TET2 expression was reported at very low levels and TET1 expression could not be detected (Page-Lariviere & Sirard 2014). Low TET1 mRNA abundance was described in oocytes and early embryos in both pig and rabbit (Lee et al 2014, Salvaing et al 2016. Conversely, TET2 was seen to be moderately expressed during oocyte maturation and early embryo pre-implantation in pig, but its higher abundance was reported in rabbit oocytes and 1-to 4-cell stage embryos (Salvaing et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In bovine oocytes, TET2 expression was reported at very low levels and TET1 expression could not be detected (Page-Lariviere & Sirard 2014). Low TET1 mRNA abundance was described in oocytes and early embryos in both pig and rabbit (Lee et al 2014, Salvaing et al 2016. Conversely, TET2 was seen to be moderately expressed during oocyte maturation and early embryo pre-implantation in pig, but its higher abundance was reported in rabbit oocytes and 1-to 4-cell stage embryos (Salvaing et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Studies in mouse, bovine, rabbit and pig reported different and sometimes contradictory patterns of TET1, TET2 and TET3 expressions during oogenesis and early development. A consensus regards Tet3 very high expression in the oocyte and zygote in all species (Iqbal et al 2011, Wossidlo et al 2011, Lee et al 2014, Page-Lariviere & Sirard 2014, Sakashita et al 2014, Salvaing et al 2016, while data on Tet1 and Tet2 are inconsistent. Sakashita and coworkers (Sakashita et al 2014) reported a significant increase in Tet3 expression during mouse oocyte growth, but failed to report the expression of Tet1 or Tet2 in growing or GV oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Superovulation in the female rabbits was induced by five subcutaneous injections of pFSH (Stimufol®, Merial, France) during the 3 days prior to mating (two 5-μg doses on the first day at 12-h intervals, two 10-μg doses on the second day at 12-h intervals, and one 5-μg dose on the third day), followed 12 h later by an intravenous administration of 30 IU HCG (Chorulon, MSD Animal Health, USA) at the time of natural mating with male New Zealand white rabbits (Reis e Silva et al 2011; Salvaing et al 2016). The zygotes were flushed from the oviducts with PBS at 19 h post-coitum (hpc) and cultured in vitro up to different stages in M199 (Sigma-Aldrich, USA) supplemented with 2.5% fetal calf serum under mineral oil (Sigma-Aldrich, USA) in an incubator at 38.5 °C under 5% CO 2 in air.…”
Section: Methodsmentioning
confidence: 99%
“…At the 16-cell stage, some NPBs (called A-NPB) displayed a less compact structure associated with RNA detection but fully functional nucleoli were only detected at the morula and blastocyst stages (Baran et al 1997). However, very few information are available concerning the nuclear organization in 3D (Yang et al 2013; Popken et al 2016) and the epigenetic marks associated with pericentromeric heterrochromatin (Brero et al 2009; Reis e Silva et al 2011; Salvaing et al 2016) during early embryonic development in rabbit. In our previous study of heterochromatin organization (Yang et al 2013), the HP1β and CENP patterns observed using immunodetection were seen to change at the time of EGA (8-cell stage).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the most extensive analysis concerned the methylome of one single chromosome (chromosome 7) and showed that embryo culture in KSOM AA resulted in a generalized hypermethylation together with greater inter locus variability compared to in vivo developed blastocyst (Wright, Brown, Brown, Casson, & Brown, ). Analysis of DNA methylation during preimplantation development by careful quantification of 5methylcytosine immunofluorescence staining in rabbit embryos cultured in two different human ART culture media (Global and ISM1/ISM2), showed that the kinetics of DNA de‐methylation varies with in vitro culture medium, none of which being close to the in vivo condition (Salvaing et al, ). Such variations in DNA methylation of non‐imprinted regions may also induce long terms effects on the adult phenotype (Morgan, Jin, Li, Whitelaw, & O'Neill, ).…”
Section: Effects Of Art Process On Early Embryo Developmentmentioning
confidence: 99%